Optimization of Online Dispute Resolution (ODR) for Legal Certainty in E-Commerce Consumer Protection in Indonesia - Devy Fitri Syahrani; Ema Nurkhaerani (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
The development of e-commerce in Indonesia has driven the need for an effective, straightforward, and affordable dispute resolution model. Online Dispute Resolution (ODR) has a clear legal basis through Law No. 30 of 1999 and Government Regulation No. 80 of 2019, but its regulations are still scattered, not yet harmonized, and not supported by adequate institutional design. This study aims to analyze the harmonization of ODR regulations in e-commerce dispute resolution and formulate a model for optimizing its implementation through the Consumer Dispute Resolution Agency (BPSK). This study applies normative legal methods based on legislative, conceptual, and case study approaches. The analysis is based on the ideas of Law in Books vs. Law in Action and Law as a Tool of Social Engineering formulated by Roscoe Pound, as well as the concept of Access to Justice developed by Mauro Cappelletti and Bryant G. Garth. The results of the study indicate that ODR regulations in Indonesia still experience disharmony in procedural, institutional, and systemic aspects, mainly due to the lack of integration between marketplace platforms, the Directorate General of PKTN, and BPSK. Platforms' internal mechanisms also tend to be closed and do not fully guarantee procedural fairness for consumers. Optimizing ODR needs to be directed towards a hybrid model that positions platforms as providers of digital evidence, while the BPSK remains an independent dispute resolution authority. This model is expected to strengthen consumer protection, increase legal certainty, and achieve effective and equitable e-commerce dispute resolution.